The Influence of Management Accounting Information Systems on Managerial Performance with Decentralization as Moderating Variables in PT. Perkebunan Nusantara II (Persero) Tanjung Morawa - Ingsun Kumala Irti; Irfan Irfan; Maya Sari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine how much influence the management accounting information system has on managerial performance with decentralization as a moderating variable at PT. Perkebunan Nusantara II (Persero) Tanjung Morawa. This study uses quantitative associative methods and data collection in this study using primary data with 40 respondents. Data analysis techniques in this study using Smart PLS. The results show that management accounting information systems have an effect on managerial performance, and decentralization strengthens the effect of management accounting information systems on managerial performance.